Strategi Perencanaan dan Pembangunan Wilayah Kota Palangka Raya Berbasis Sektor Ekonomi Unggulan - Vidya Puspita (Ecoplan, 2022)
In order to support regional development efforts, comprehensive planning is needed. One of which is by strengthening the leading economic sectors in the region, which can become potential that optimizes the development process. This study aims to identify potential basic economic sectors in order to support the planning & development of Palangka Raya City. The analysis was carried out using secondary and time series data (in 2018 and 2020). It examined the Gross Regional Domestic Product (GRDP) of Palangka Raya City and Central Kalimantan Province collected from the Center Bureau of Statistics publications. The analytical tools used in this research were LQ and shift-share analysis. Based on the LQ analysis, the most dominant sectors supporting economic growth in Palangka Raya City are electricity & gas procurement (4.61), government administration of defense and mandatory social security (3.38), and the provision of accommodation, food, and drink (2.70). Meanwhile, the shift-share analysis revealed that 3 (three) sectors are growing faster, more advanced, and more competitive compared to other regions in Central Kalimantan Province. These sectors include the electricity & gas procurement sector (0.56), information & communication (0.29 ), as well as health services & social activities (0.22). Based on the priority scale, which is a combination of LQ and shift-share analysis, the basic economic sectors in Palangka Raya City are the electricity and gas procurement sector as well as the defense and social security government administration sector. It is hoped that the Palangka Raya City government can coordinate with Hiswana Migas to hold an SPPBE that can absorb a large number of workers. Corporates should also be able to partner with the government in supporting the provision of local government needs effectively and efficiently.